The Scania Accelerated Intermittent Theta-burst Implementation Study (SATIS)–Lessons from an accelerated treatment protocol - Marcus Persson; Viktor Fabri; Alexander Reijbrandt; Annika Lexén; Hans Eriksson; Pouya Movahed Rad (PLoS ONE, 2025)
Background and objective The Scania Accelerated Intermittent Theta-burst Implementation Study (SATIS) aimed to investigate the tolerability, preliminary effectiveness, and practical feasibility of an accelerated intermittent theta burst stimulation (aTBS) protocol in treating depression. Methods We used an open-label observational design, recruiting 20 patients (aged 19–84 years) from two public brain stimulation centers in Sweden. During the five-day treatment period and at a follow-up visit after 30 days we closely monitored adverse events and collected self-rated side effect data. Objective (MADRS, CGI) and subjective (MADRS-S) measures of symptoms and functioning (EQ-5D) were also assessed. Feasibility was evaluated using direct patient ratings combined with a qualitative approach evaluating staff experience. Results All patients reported adverse events at some point, the most common being headache (18/20 patients), but they were generally transient. MADRS scores decreased from 28.4 (min = 17, max = 38. SD = 6.9) at baseline to 20.0 (min = 1, max = 42. SD = 11.6) after the last day of treatment. 25% (n = 5) met the response criteria, with a mean time to response of 2.2 days (min = 1, max = 3. SD = 1.1). The practical arrangements surrounding this new treatment proved challenging for the organization, but patients reported few practical problems. Conclusion SATIS provided further insights into the potential benefits and challenges associated with aTBS protocols. Effectiveness and drop-out rates were comparable to national data of conventional iTBS, but with a markedly faster time to response. More resources were required than anticipated, increasing the clinical workload.